Effect of Vitamin K Supplementation on Glycemic Control: A Systematic Review and Meta-Analysis of Clinical Trials - Shahdadian, Farnaz; Mohammadi, Hamed; Rouhani, Mohammad Hossein (Hormone and Metabolic Research, 2018)
Type 2 diabetes mellitus (T2DM) is one of the most important public health issues. Vitamin K supplementation might have favorable effect on risk factors of T2DM. The aim of this study was to perform a systematic review and meta-analysis of interventional studies to examine the effect of vitamin K supplementation on glycemic indices. A systematic search was performed in electronic databases including PubMed, Science Direct, ProQuest, Institute of Scientific Information Web of Science, and Google scholar up to July 2017. We used a random effects model to estimate pooled effect size of fasting blood sugar (FBS), 2-h oral glucose tolerance test (2-h OGTT), fasting insulin (FINS), and homeostasis model assessment-estimated insulin resistance (HOMA-IR). Five clinical trials (533 participants) fulfilled the eligibility criteria of the present meta-analysis. Overall, meta-analysis could not show any beneficial effect of vitamin K supplementation on FBS (–0.91 mg/dl, 95% CI: –2.57, 0.76, p=0.28), FINS (–0.35 μIU/ml, 95% CI: –1.70, 1.00, p=0.61), HOMA-IR (–0.06, 95% CI: –0.32, –0.19, p=0.63), and 2-h OGTT (–4.00 mg/dl, 95% CI: –20.00, 11.99, p=0.62). Sensitivity analysis showed that overall estimates were not affected by elimination of any study. We did not observe any evidence regarding publication bias. In conclusion, vitamin K supplementation had no signiﬁcant effect on glycemic control in healthy subjects. However, further studies should be performed on diabetic and pre-diabetic patients to determine the effect of vitamin K supplementation on impaired glycemic control.
Keywords: vitamin K; fasting blood sugar; serum insulin; glycemic control; meta-analysis